The Croatin and Bosnian language in BiH (1992–1995) in light of the theory of linguistic imperialism: Language policy in education - Hodžić, Jasmin (Slavia Centralis, 2021)
The paper discusses the Croatian language and the Bosnian language in the Republic of Bosnia and Herzegovina (1992–1995) in the context of the discussion on language rights and in the context of the discussion on language discrimination, especially regarding the theory of linguistc justice and the theory of linguistic imperialism, which is also directly related to the issue of native language in education and pedagogical practice, both in the past and today. An analysis of the social arrangement of language issues is provided with concrete examples of the contents of legal documents in the first half of the 1990s, which is connected to the language in education and wider society, with a special analysis of the specific social practices. This is an analysis of the present practically existing discriminatory, assimilating and segregationist models of education, as opposed to a desirable integration, non-segregationist and non-discriminatory education system.